The Influence of Work Life Balance Benefits and Working Expectation on Job Pursuit Intention with Employer Attractiveness as a Mediating Variable - Aura Neema Ramadhani; Sartikah Sartikah; Suryo Hadi Wira Prabowo (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2025)
This research focuses on investigating the impact of Work-Life Balance Benefits and Working Expectations on Job Pursuit Intention, with Employer Attractiveness as a mediating variable. The method used by the author is a quantitative method, by applying Structural Equation Modeling Partial Least Square (SEM-PLS). The population of this study consists of all Informatics Engineering students at Brawijaya University, while the sample includes 275 students from the Informatics Engineering program at the university. The results reveal that Working Expectations and Employer Attractiveness have a positive and significant effect on Job Pursuit Intention. However, Work-Life Balance Benefits do not have a significant effect on Job Pursuit Intention. Nonetheless, Employer Attractiveness successfully mediates the relationship between both variables (Work-Life Balance Benefits and Working Expectations) and Job Pursuit Intention. This research provides insights for companies to enhance their appeal by improving work-life balance initiatives and meeting the expectations of Generation Z job seekers.